Upaya Penegakan Hukum terhadap Pelaku Tindak Pidana Perjudian Online - Ferdian Atma Wijaya (Pusat Riset dan Inovasi Nasional, 2025)
Law enforcement against perpetrators of online gambling crimes is one of the big challenges in the current digital era. The increasingly widespread online gambling offers easy access for the public, but also has the potential to cause negative social and economic impacts. This study aims to analyze law enforcement efforts carried out against perpetrators of online gambling crimes, both in terms of applicable laws and regulations and the operational steps of law enforcement officials. Based on research results, law enforcement against online gambling still faces various obstacles, including technological limitations in tracking illegal transactions, as well as regulations that are not yet fully effective in dealing with the complexity of cybercrime. The government through the police, Ministry of Communication and Information, and other relevant authorities have attempted to block access to online gambling sites, but implementation is still not optimal. Therefore, more intensive cooperation is needed between law enforcement agencies, strengthening regulations, and increasing technological capacity to effectively tackle online gambling crimes.